Naprezanja kolosiječne rešetke u uvjetima eksploatacije - Stipetić, Antun; Golubić, Jasna (Promet - Traffic&Transportation, 2012)
The study of the behavior of different track panel structures on the lines of the Croatian Railways has been completed in regular conditions of utilization. The subject research has been conducted by measurement of strain in straight and curved track sections.